2008
DOI: 10.1016/j.rmed.2008.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Role of airway epithelial cells in development of asthma and allergic rhinitis

Abstract: Asthma and allergic rhinitis frequently coexist in the same patient. There is a similarity and variation as well as potential relationship between asthma and allergic rhinitis. There is an increasing evidence to suggest a major involvement of airway epithelial cells in the pathogenesis of asthma and allergic rhinitis. The present review describes the importance of the airway epithelial cell in the development of allergic airway diseases, its role as the primary airway defense against exposure of the airway and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 70 publications
1
76
1
Order By: Relevance
“…*P Ͻ 0.05 compared with all other groups. (32,50) can produce IL-5, IL-12, IL-13, and CCL24 (17,27,45,52), which suggests that nonhematopoietic PTP1B may be necessary for production of these cytokines in nonhematopoietic lung cells during allergic inflammation. This reduction in cytokines in allergen- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…*P Ͻ 0.05 compared with all other groups. (32,50) can produce IL-5, IL-12, IL-13, and CCL24 (17,27,45,52), which suggests that nonhematopoietic PTP1B may be necessary for production of these cytokines in nonhematopoietic lung cells during allergic inflammation. This reduction in cytokines in allergen- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, bronchial epithelial cells, fibroblasts, smooth muscle cells, and mast cells have the potential to produce TSLP in human [96,99]. Wang et al [100] reviewed the interaction between ligands and epithelial cells as follows, since exposure of the airway inflammatory stimuli through activation of epithelial Toll-like receptor (TLR)s to provide an important link between innate immunity and allergic disease. Additionally, airway epithelial cells can act as inflammatory promoters capable of directing DCs towards a Th2 response.…”
Section: Environmental Factors In Driving Goblet Cell Responsesmentioning
confidence: 99%
“…TSLP production can be induced in airway epithelial cells by ligands that activate TLR2, TLR3, TLR8 and TLR9 to release TSLP protein, and TLR8 and TLR9 to stimulate TSLP gene transcription through NF-kB activation [100]. Ligands (TLRL) capable of activating these TLRs include bacterial lipoteichoic acid and peptidoglycans from bacteria (TLR2), single stranded (TLR8) and double-stranded (TLR3) viral RNA, and CpG DNA motifs in both viruses and bacteria (TLR9).TLR activation can also be initiated by other factors such as viruses, dustsand chemicals [100]. TSLP activated immature mDCs rapidly express TSLP receptor (TSLPR) and DCs undergo maturation in response to TSLP [96].…”
Section: Environmental Factors In Driving Goblet Cell Responsesmentioning
confidence: 99%
“…In the past decade it has become evident that the airway epithelium is an important player in the regulation of immune responses through release of cytokines, chemokines and growth factors [24]. Many reports have shown that the release of chemokines is altered in asthmatic patients at baseline level as well as after bronchial challenge [25][26][27].…”
Section: Figurementioning
confidence: 99%